The Development and Pilot Evaluation of ECHO Mental Health for Adults with Intellectual and Developmental Disabilities. Issue 1 (2nd January 2023) - Lunsky, Yona; Bobbette, Nicole; Durbin, Janet; Gonzales, Angela; Grier, Elizabeth; Iruthayanathan, Renisha; Mia, Nadia; Pereira, Cheryl; Steel, Lee; Thakur, Anupam; Thomson, Kendra; Sockalingam, Sanjeev
ABSTRACT: Introduction: Health and social service providers have limited expertise with regard to assessing and treating psychiatric disorders in adults with intellectual and developmental disabilities. The aim of this study was to describe the development and pilot evaluation of a virtual capacity-building program (Project ECHO) focused on supporting the mental health of adults with these disabilities in Ontario, Canada. Method: The pilot program consisted of 12 weekly 1.5 hour sessions hosted through a video-conferencing platform, with a combined focus of didactic teaching and case-based learning, led by an interprofessional team of subject matter experts. The program evaluation was informed by Moore's evaluation framework for continuing medical education. Ongoing attendance tracking, weekly surveys, and pre-post questionnaires were used to evaluate participation, satisfaction, learning and self-efficacy, and practice change. Results: The program included 62 participants from across Ontario, Canada, from both the health and social service sectors. Seventy-three percent of participants attended six or more sessions, with high participant satisfaction ratings seen with the program. A statistically significant improvement in self-efficacy mean scores of 14.7% was observed pre-post. Seventy-four percent of respondents indicated that they had changed their practice because of participating in this ECHO. Conclusion: Good participant retention, satisfaction, and increased confidence suggests this cross-sector virtual medical education program may have value for health and social service providers as they support the mental health of adults with intellectual and developmental disabilities.